Conceptual and Methodological Questions on the Changing Paradigms of Governance - Sapkota, Mahendra (Journey for Sustainable Development and Peace Journal, 2023)
Globally, governance studies have been an emerging paradigm of research and scholarly debate in social sciences. This paper takes this debate as an entry point and aims to analyze its metaphysical construction in terms of ontology, epistemology, and methodology. Data and materials used in the paper are based on the sources of secondary literature. The findings reveal that the political construction of governance is now becoming complex in contemporary societies and it has then adjoined with social, economic, and regional issues in particular. The paper concludes that governance is a contested notion that is moving around different concepts, theories, methodologies, and paradigms. The paper, therefore, is expected to contribute to the governance study in particular along with different disciplines of social science research in general.